The Psychological Impact of Covid 19 Restrictions on Athletes: A Descriptive Analytical Study - Hermahayu, Hermahayu; Faizah, Rayinda; Candra, Adiska Rani Ditya (KEMAS: Jurnal Kesehatan Masyarakat, 2022)
Restrictions on community activities implemented by the government to resolve the spread of the Covid 19 virus have closed several sports facilities, deactivated sports clubs, and national and international sports competitions have been delayed or canceled. This study aims to explore the effect of these restrictions on the psychological condition of athletes. This research uses the descriptive analysis method by surveying to obtain information from the respondents. There are three things to examine (i.e. athletes’ feelings about the condition, how they deal with negative feelings that arise, and the actions they take during restriction). The subjects of this study were 179 athletes from 22 sports associations managed by regional governments and sports committees. The survey method was used in this research. Open questionnaires are sent to athletes to fill out. The results can be used as a recommendation for coaches and the government.